2008 IEEE International RF and Microwave Conference 2008
DOI: 10.1109/rfm.2008.4897359
|View full text |Cite
|
Sign up to set email alerts
|

Circuit modeling of an UWB patch antenna

Abstract: An Ultra wideband (UWB) patch antenna is analyzed in this paper. The design uses FR-4 substrate with dielectric constant of 4.9 and thickness of 1.6 mm. Circuit model of such antenna is developed under AWR Microwave Office environment. Obtained results from simulating the antenna in CST Microwave Studio are then compared with the results taken from the Circuit Model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The designed printed rectangular monopole antenna is simulated using the IE3D electromagnetic simulator from Zeland, Inc., USA. The lumped equivalent circuit of the proposed printed rectangular monopole antenna is obtained as presented in [14,15]. The lumped equivalent circuit model is simulated in the advanced design system (ADS) software.…”
Section: Printed Monopole Antennamentioning
confidence: 99%
“…The designed printed rectangular monopole antenna is simulated using the IE3D electromagnetic simulator from Zeland, Inc., USA. The lumped equivalent circuit of the proposed printed rectangular monopole antenna is obtained as presented in [14,15]. The lumped equivalent circuit model is simulated in the advanced design system (ADS) software.…”
Section: Printed Monopole Antennamentioning
confidence: 99%
“…Figure 2(b) is the representation of the steps width W 1 and W 2 . From [17] it has been shown that the steps in the structure will increase the bandwidth. This is because each step mimics a resonance patch Table 1.…”
Section: Antenna and Pi Matching Network Designmentioning
confidence: 99%